(x*x)-6x=0

Simple and best practice solution for (x*x)-6x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x*x)-6x=0 equation:


Simplifying
(x * x) + -6x = 0

Multiply x * x
(x2) + -6x = 0
x2 + -6x = 0

Reorder the terms:
-6x + x2 = 0

Solving
-6x + x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'x'.
x(-6 + x) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(-6 + x)' equal to zero and attempt to solve: Simplifying -6 + x = 0 Solving -6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + x = 0 + 6 x = 0 + 6 Combine like terms: 0 + 6 = 6 x = 6 Simplifying x = 6

Solution

x = {0, 6}

See similar equations:

| 92*67*67*67*98*75*57*23*34= | | 5y+6=6y-14 | | 2/5b-6-2 | | ln(3x-18)=8 | | 2(2x+2)=4x+6-2 | | (x^2-5)(x^2-4x+5)=0 | | 12x+12-x-5=92 | | 106=41(2x+4y) | | 5+x=87 | | 2-k=0 | | 2(x^2-5)(x^2-4x+5)=0 | | a^2+a+a^2=0 | | 36/3/5 | | 155.00x+7500.00=92440.00 | | X*2+5=-14 | | 39.55+0.20m=80 | | x^(2/3)-1 | | 15+3=18y | | 5b+3(4+5b)= | | x^2=7-2x | | 2x^7-16x^6+12x^5= | | 5+3(4+5)= | | (-15/2)(-1) | | 7x+1x=28+9x | | (324*80)= | | 2x^4-8x^3+40x-50=0 | | 7x+1x=14+9x | | 2.583+(-5.399)= | | 7x+1x=28+9 | | 3x/5-9=27 | | 2x-3=69-7x | | 4x^2=25x+21 |

Equations solver categories